The Invigoration Techniques of Nyamplung (Calophyllum inophyllum L.) Seeds During the Storage - Naning Yuniarti (Jurnal Wasian, 2020)
Nyamplung (Calophyllum inophyllum L.) is one of forestry plant that has double benefits (economic and ecological). One of the problems faced in the development of nyamplung is its recalcitrant seed, which can not be stored for long periods. To increase the viability of nyamplung seed during storage, seed invigoration techniques are required. Invigoration is the treatment given to seeds before planting with the aim of improving germination and growth of sprouts. The purpose of this research is to know the proper invigoration technique on nyamplung seed during storage. The experimental design of the research was used Completely Randomized Design (CRDL) with factorial. There are 2 factors treatments: the first factor of: Invigoration treatment (control, osmoconditioning with soaking in aquades for 24 hours, osmoconditioning with immersion in PEG-6000 concentration 15 % for 24 hours, matriconditioning with moisture of newspaper (CD) for 2 hours, and matriconditioning with moisture ash scrub for 2 hours) and savings period factor the second factor of period of storage (0, 1, and 2 months). The research was conducted with replication is 4 times, @ each with 50 seeds of seed. The observation of germination is done after normal sprout growth, which it has of a pair of leaves. The parameters observed were germination and germination rate. The results showed that the proper invigoration technique on nyamplung seed during storage was the treatment of matriconditioning with moisture of newspaper (CD) for 2 hours. With this treatment it can increase the viability of seed nyamplung (germination) at 42 % and vigor seed (germination rate) at 0,56 % /etmal. results at the end of the abstract. The longer the storage period will cause the value of germination and the speed of germination to decrease.Keywords: seed, invigoration, nyamplung (Calophyllum inophyllum L.), recalcitrant, viabil